2019
DOI: 10.1039/c9sc01380f
|View full text |Cite
|
Sign up to set email alerts
|

On the encapsulation and assembly of anticancer drugs in a cooperative fashion

Abstract: In this study, we report the remarkable recognition and assembly characteristics of D3h symmetric basket 16− containing two adjoining and nonpolar cavities with six biocompatible GABA residues at their northern and southern termini.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 58 publications
(61 reference statements)
0
14
0
Order By: Relevance
“…)e ncompass asymmetric, concave,n onpolar,a nd functionalized spaces for accommodating targeted molecules,our methodology opens aw ay for constructing comparable interiors within artificial molecules in ap redictable and stereoselective manner. Examining chiral molecular recognition within such uniquely structured and customizable environments is to be pursued with an eye set on creating more effective supramolecular catalysts [54] or soft nanostructured materials [29] capable of sequestering toxicants [55] and delivering pharmaceuticals. [32a, 56]…”
Section: Forschungsartikel Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…)e ncompass asymmetric, concave,n onpolar,a nd functionalized spaces for accommodating targeted molecules,our methodology opens aw ay for constructing comparable interiors within artificial molecules in ap redictable and stereoselective manner. Examining chiral molecular recognition within such uniquely structured and customizable environments is to be pursued with an eye set on creating more effective supramolecular catalysts [54] or soft nanostructured materials [29] capable of sequestering toxicants [55] and delivering pharmaceuticals. [32a, 56]…”
Section: Forschungsartikel Conclusionmentioning
confidence: 99%
“…[24] Alongside these and other important advances, [25] we herein describe am ethodology for constructing ABC molecular baskets in astereoselective manner from A, B,and C building blocks (Figure 1B). So far, C 3 symmetric baskets have been used for studying gated molecular recognition [26] and allostery [27] but also probed as hosts for the encapsulation of nerve agents, [28] pharmaceuticals, [29] fullerenes, [30] hydrocarbon gases, [30][31] and other functional compounds. [32] Forthe first time, the side wall of these concave cavitands can now be selected to carry different aromatics,forming acustomizable nonpolar pocket, with desired functional groups at the rim (Figure 1B) to greatly expand the utility of basket-like hosts.…”
Section: Introductionmentioning
confidence: 99%
“…Nanosized 1 (d = 3.0 nm and V = 5 nm 3 ) is a truncated [4+4] tetrahedron 28 with four trigonal panels made of triphenyl benzenes and four vertices composed of abiotic cavitands, baskets, 29 known to act as allosteric hosts 27 capable of trapping haloalkanes, 30 cationic molecules, 31 nerve agents, 32 pesticides, 33 and anticancer drugs. 34 Accordingly, we reasoned that obtaining non-collapsible CBCs of type 1 and developing a method for their transient formation via consumption of chemical fuel will set the stage for examining temporal control of their action 17 resembling GRoEL chaperone in Figure 1C. 18 For the first time, we herein describe a method to drive the out of equilibrium formation of covalent basket cages in a tunable manner using an acidic chemical fuel in organic media.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, recent studies have shown that two limiting mechanisms are not mutually exclusive and can take place concurrently [8] . For a large variety of abiotic hosts, [2b,c, 9] only a handful of studies [10] address the two mechanistic paradigms. Raymond‐Bergman‐Toste [11] and Jiang [12] teams have recently measured kinetics by which an encapsulation equilibrium is established to find that CS dominates entrapments promoted by self‐assembled metallacages and naphthotube macrocycles with guest molecules in excess.…”
Section: Introductionmentioning
confidence: 99%